Ethical Aspects in Knowledge Organization A Discourse Analysis at ISKO International Events - Evangelista, Isadora Victorino [UNESP]; Bragato Barros, Thiago Henrique; Lykke, M.; Svarre, T.; Skov, M.; MartinezAvila, D. (Ergon-verlag, 2020)
The present research intended to analyse what is the perception from International Society for Knowledge Organization (ISKO) about Ethical studies in the field. To do that, was applied a discourse analysis in the papers with social contets presented in the international events of the society. Was possible to see a criticism to misrepresentation in languages considered universal, the exclusion of marginalized groups in society, and the change of paradigms of information access from the technological development.